The socio-demographics and pattern of atherosclerosis of hospitalized adult patients without SARS-Cov-2 infection in a new tertiary hospital in Malaysia - Alati, Mohamad Ahmad; Khalid, Bahariah; Mohd Yusof, Barakatun Nisak; Appannah, Geeta (Qassim University, 2022)
Background: Atherosclerosis, a chronic inflammatory condition of the arterial intimal wall projected globally to impact healthcare significantly. The pattern of atherosclerosis, namely the atherosclerotic disease and atherosclerotic risk, may or may not be the reason for hospitalization; nevertheless, they have ongoing atherosclerosis that may progress over the years. Studies have shown that both patterns of atherosclerosis play an essential role in conferring poor prognosis and contributing to the leading cause of death. We embark on a study to analyze the socio-demographic and pattern of atherosclerosis of adult patients without SARS-Cov-2 infection admitted to a new tertiary hospital in Malaysia. We exclude patients who are predicted to have a high possibility of death or discharge within 24 hours, lactating mothers, oncology patients and non-Malaysian citizens; Methods: This prospective cross-sectional study recruited general medical and surgical ward adult patients between 9th October and 1st January 2021. The data were collected using face-to-face interviews with the patients and from the medical records. For our research, we identify the patient's affirmation on having atherosclerosis, atherosclerotic disease, atherosclerotic risks, the reason for admission and their discharge outcome.